Roux-en-Y Gastric Bypass Acutely Decreases Protein Carbonylation and Increases Expression of Mitochondrial Biogenesis Genes in Subcutaneous Adipose Tissue - Jahansouz, Cyrus (Obes Surg, 2015)
BACKGROUND: Mitochondrial dysfunction in adipose tissue has been implicated as a pathogenic step in the development of type 2 diabetes mellitus (T2DM). In adipose tissue, chronic nutrient overload results in mitochondria driven increased reactive oxygen species (ROS) leading to carbonylation of proteins that impair mitochondrial function and downregulation of key genes linked to mitochondrial biogenesis. In patients with T2DM, Roux-en-Y gastric bypass (RYGB) surgery leads to improvements in glycemic profile prior to significant weight loss. Consequently, we hypothesized that improved glycemia early after RYGB would be paralleled by decreased protein carbonylation and increased expression of genes related to mitochondrial biogenesis in adipose tissue. METHODS: To evaluate this hypothesis, 16 obese individuals were studied before and 7–8 days following RYGB and adjustable gastric banding (AGB). Subcutaneous adipose tissue was obtained pre- and post-bariatric surgery as well as from eight healthy, non-obese individual controls. RESULTS: Prior to surgery, adipose tissue expression of PGC1α, NRF1, Cyt C, and eNOS (but not Tfam) showed significantly lower expression in the obese bariatric surgery group when compared to lean controls (p<0.05). Following RYGB, but not after AGB, patients showed significant decrease in HOMA-IR, reduction in adipose protein carbonylation, and increased expression of genes linked to mitochondrial biogenesis. CONCLUSIONS: These results suggest that rapid reduction in protein carbonylation and increased mitochondrial biogenesis may explain postoperative metabolic improvements following RYGB.